Leo Tolstoy’s perspective on Islam and Prophet Muhammad - Abdul Razak, Mohd Abbas (Human Assistance & Development International Inc. (HADI Inc.), 2025)
Russia occupies a special place when we discuss European literature. It took the lead before England and France came into the picture. When we think about the great giants in Russian literature, Leo Tolstoy (1828–1910) and Feodor Dostoevsky (1821–1881) come to mind. Besides these two, the literary men who deserve mention here would include Alexander Pushkin (1799–1837), who is deemed the Father of Russian Literature, Nikolai Gogol (1809–1852), Ivan Turgenev (1818–1883), and Anton Chekhov (1860–1904). Though Tolstoy worked on many writings, he is well-known to the world for two of his epic novels, one was War and Peace, published in 1869 and the other Anna Karenina, which came to see the light of day in 1877. It is not an exaggeration to say that these two master pieces skyrocketed his fame and glory. In the given space of this article, I would like to focus on Tolstoy, for the reason that he spoke on Islam, Prophet Muhammad (SAW), and the Muslims. Besides his other novels, Hadji Murad, which was published posthumously, is a literary work based on the real-life story of a Chechen rebel leader. Though stories of Muslims of the Caucasus are scattered throughout Tolstoy’s works, they occupy a significant place.